2002
DOI: 10.4049/jimmunol.168.8.4063
|View full text |Cite
|
Sign up to set email alerts
|

Store-Operated Calcium Entry in Human Neutrophils Reflects Multiple Contributions from Independently Regulated Pathways

Abstract: Human polymorphonuclear neutrophil (PMN) responses to G protein-coupled chemoattractants are highly dependent upon store-operated Ca2+ entry (SOCE). Recent research suggests that SOCE currents can be mediated by a variety of related channel proteins of the transient receptor potential superfamily. SOCE has been regarded as a specific response to depletion of cell calcium stores. We hypothesized that net SOCE might reflect the contributions of more than one calcium entry pathway. SOCE was studied in normal huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
80
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 34 publications
(23 reference statements)
7
80
0
Order By: Relevance
“…One likely participant is inositol 1,4,5-triphosphate, which is generated during FMLP stimulation of neutrophils (54). Inositol 1,4,5-triphosphate promotes Ca 2ϩ release from the ER, which in turn triggers store-operated Ca 2ϩ influx across the plasma membrane (55). Recently, phosphoinositol 3-kinase-␥ knockout mice have been shown to be defective in orientation in the presence of a chemotactic factor (56); this defect may be associated with the second clockwise Ca 2ϩ wave.…”
Section: Discussionmentioning
confidence: 99%
“…One likely participant is inositol 1,4,5-triphosphate, which is generated during FMLP stimulation of neutrophils (54). Inositol 1,4,5-triphosphate promotes Ca 2ϩ release from the ER, which in turn triggers store-operated Ca 2ϩ influx across the plasma membrane (55). Recently, phosphoinositol 3-kinase-␥ knockout mice have been shown to be defective in orientation in the presence of a chemotactic factor (56); this defect may be associated with the second clockwise Ca 2ϩ wave.…”
Section: Discussionmentioning
confidence: 99%
“…Blood was spun (150 ϫ g for 10 min) to remove platelet-rich plasma. Cells were then layered onto equal volumes of Polymorphoprep medium (Robbins Scientific) and separated as we have described (8,17,22). PMN layers were removed and mixed with an equal volume of 0.45% sodium chloride solution to restore osmolarity for 5 min.…”
Section: Pmn Isolationmentioning
confidence: 99%
“…PMN lack voltage-gated calcium channels (19) and we have shown that PMN mobilize external Ca 2ϩ via mechanisms that mobilize multiple TRPC proteins to the cell membrane (8,9). Cytoskeletal alterations that prevent TRPC membrane localization block entry of calcium into PMN (9) and TRPC are known to localize to rafts in PMN and other cell types (20,21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The cation influx mediated by SOCC is highly Ca 2ϩ -specific. Other divalent cations such as Ba 2ϩ and Sr 2ϩ are also permeable albeit at a much slower rate (3,7). In the absence of divalent cations, it has been reported that the SOCC becomes permeable to Na ϩ (8,9).…”
Section: ؉mentioning
confidence: 99%